6 wooden sticks and one long wooden border
so totally 7 wood is there
I think this correct
<h3>
Answer:</h3>
f(x) = -(x -2)² +3
<h3>
Step-by-step explanation:</h3>
We can fill in the vertex (h, k) values immediately in the vertex form ...
... f(x) = a(x -h)² +k
To find the value of a, we solve the equation for a at some point other than the vertex. The given point is (0, -1), so we can use that:
... -1 = a(0 -2)² +3
... -4 = 4a . . . . . . . . . subtract 3, simplify
... -1 = a . . . . . . . . . . . divide by 4
Now, we know the function is ...
... f(x) = -(x -2)² +3
Answer:
idk really sry
Step-by-step explanation:
When the bases are diffenrent and the exponents of a and b are the same, we can multiply a and b first:
a n ⋅ b n = (a ⋅ b) n
Example:
32 ⋅ 42 = (3⋅4)2 = 122 = 12⋅12 = 144
When the bases and the exponents are different we have to calculate each exponent and then multiply:
a n ⋅ b m
Example:
32 ⋅ 43 = 9 ⋅ 64 = 576